DIFFERENTIAL PROPERTIES OF SYMMETRIC BLOCK CIPHERS WITH ROUND KEY MODULAR OPERATIONS OTHER THAN XOR - Lysytska, I.V.; Nastenko, A.A. (Radio Electronics, Computer Science, Control, 2013)
Symmetric block ciphers differential properties with various round key operations are considered. It is shown that known ciphers with round operations other than XOR after small initial encryption rounds acquire random substitution properties of correspondent degree, but they achieve stationary maximal value two times smaller than maximal value acquired for round operation as bitwise XOR. It is concluded that application of round operations other than XOR does not lead to significant growth of provable cipher strength. It is mentioned that all iterative ciphers independently of round key operation type give the same maximal values of full differentials according to difference computation operation as bitwise XOR.